2019
DOI: 10.1186/s12876-019-0986-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Helicobacter pylori and its virulence genes (cagA, dupA, and vacA) among patients with gastroduodenal diseases in Chris Hani Baragwanath Academic Hospital, South Africa

Abstract: Background The global prevalence of H. pylori approaches 50%, with prevalence rates between 20 and 40% in developed countries and up to 90% in Africa and other developing nations of the world. Development of H. pylori -associated diseases is determined by a number of virulence factors. This study aimed at determining the prevalence of H. pylori infections and virulence genes ( cag A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
2
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 65 publications
9
32
2
11
Order By: Relevance
“…The study, however, concluded that no association existed between the studied genotypes and duodenal ulcer disease in that particular population [139]. These reported observations on prevalence are consistent with studies in India (96% among duodenal ulcer patients), [140] Gauteng (87% among asymptomatic children age between 6 and 15 years), [141] Alaskans-US (85%), [142] China (89.3% in patients with upper gastrointestinal diseases), and Taiwan (83% in isolates from patients with chronic gastritis and peptic ulcer) [143]. Another report in Nigeria by Mnena et al [86], however, identified only 29% out of 22 H. pylori positive patients to have the cagA gene.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The study, however, concluded that no association existed between the studied genotypes and duodenal ulcer disease in that particular population [139]. These reported observations on prevalence are consistent with studies in India (96% among duodenal ulcer patients), [140] Gauteng (87% among asymptomatic children age between 6 and 15 years), [141] Alaskans-US (85%), [142] China (89.3% in patients with upper gastrointestinal diseases), and Taiwan (83% in isolates from patients with chronic gastritis and peptic ulcer) [143]. Another report in Nigeria by Mnena et al [86], however, identified only 29% out of 22 H. pylori positive patients to have the cagA gene.…”
Section: Resultssupporting
confidence: 77%
“…In Nigeria, Smith et al detected 98% of vacA s1 in 40 H. pylori strains [139] while Harrison et al found 92.8% detectable vacA levels [61] similar to the 90.6% obtained in South Africa [141]. In the study by Harrison et al, a bulk of the isolates harbored the vacA s1, m2 genotype, followed by the s1, m1 genotype.…”
Section: Resultsmentioning
confidence: 79%
“…The vacA genotypes (allelic variations) are significantly different in each country and previous studies have confirmed important geographic differences in these virulence factors [27,28,29]. Among different genotypes, infection with H. pylori strains containing vacA s1m1 type was strongly associated with increased risk of gastric cancer or PUD [8,30,31]. In our study, most frequent allelic combination of vacA gene were s1am2 —38.7% and s2m2 —32.3%, that was similar to previous Polish studies [23,24,32]; however, statistically significant associations between vacAs1m1 type and GAST and PUD patients were observed ( p = 0.042 and p = 0.038, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In the northern part of Spain, dupA was more prevalent in mild diseases (peptic ulcer) than severe diseases (GC)[ 62 ]. In Switzerland and South Africa, dupA of H. pylori was not associated with severe gastritis or DU[ 63 , 64 ].…”
Section: Discrepancies Of Dupa With Clinical Outcomentioning
confidence: 99%